ROLE OF TRANSVAGINAL SONOGRAPHY IN ASSESSMENT OF ABNORMAL UTERINE BLEEDING IN PERIMENOPAUSAL AGE GROUP - Najeeb, Riffat; Awan, Azra Saeed; Bakhtiar, Umber; Akhter, Sadia (Journal of Ayub Medical College Abbottabad, 2010)
Background: Abnormal uterine bleeding (AUB) is a common problem which prompts more than 20% of all visits to outpatient clinics, and may account for more than 25% of all hysterectomies. The objective of this study was to determine the role of transvaginal ultrasonography in women of perimenopausal age group presenting with abnormal uterine bleeding. Methods: This descriptive study was conducted in Department of Obstructs and Gynaecology, Railway General Hospital, Rawalpindi. One hundred and forty-one women who attended the gynaecology clinic with abnormal uterine bleeding (menorrhagia, intermenstrual bleeding, or postcoital bleeding) between 40-47 years of age from January 2006 and April 2007 were included in this study. The mean age was 44 years. Results: Among 141 women endometrial lesions were detected in 77 cases on histopathology after Dialatation and Curettage (D&C), while 57 (40.42%) of these were confirmed on transvaginal ultrasongraphy as an endometrial pathology prior to this invasive procedure. Among the 64 remaining patients, showing normal proliferative endometrium on histopathology, 46 cases (71.87%) showed no abnormality on tranvaginal examination. Conclusion: Transvaginal sonography can be safely used as an initial investigation in the management of abnormal uterine bleeding as it is a noninvasive procedure for the detection of endometrial pathology. The incidence of detection of an abnormal pathology by ultrasongraphy is high when focal lesions as fibroids, polyps or foreign body is concerned. Dilatation and curettage being a blind procedure requires hospitalization and general anaesthesia which can be safely replaced by an alternate valid, safe and non-invasive technique for evaluating the endometrial pathology in women of perimenopausal age group with abnormal uterine bleeding. Keywords: Abnormal Uterine Bleeding (AUB), Transvaginal Sonography (TVS), Dilatation and Curettage (D&C), Perimenopasual